Rare bird documentation form for Peregrine Falcon at McCallsburg in 1986 - Proescholdt, Market al (1986)
Rare bird documentation form for a Peregrine Falcon at McCallsburg in Story County, IA on October 1, 1986. Epson - sheet feed